(untitled) (IASH Indian Journal of Arid Horticulture, 2025)
Aonla, an important indigenous minor fruit crop, is highly valued for its rich nutrient content. However, the increasing demand for its planting material remains unmet due to poor seed germination and seedling growth. Thus, there is an urgent need to standardize techniques to improve seed germination and seedling development. The current study aims to overcome seed dormancy and to enhance germination in aonla seeds. An experiment was carried out at the College of Horticulture, Venkataraman nagudem from January 2022 to May 2022, using a Factorial Randomized Block De sign with three replications, comprising 16 treatment combinations. Aonla seeds were treated with GA3 at concentrations of 300, 500, and 700 ppm for soaking periods of 12 and 24 hours under shade net and polyhouse, along with a control treatment that involved soaking in water for 24 hours. The results indicated that the combination of seed priming with GA3 @ 500 ppm for 24 hours and polyhouse conditions recorded the best outcomes, with minimum number of days to germinate (7.93 days), number of leaves (29.30), seedling diameter (6.36 mm), root length (17.50 cm) and number of roots per seedling (36.00) and survival percentage (89.32%). This study will help boost the commercial cultivation of aonla, providing significant benefits for growers.